2000
DOI: 10.1103/physreva.61.042901
|View full text |Cite
|
Sign up to set email alerts
|

Secondary-electron yields and their dependence on the angle of incidence on stainless-steel surfaces for three energetic ion beams

Abstract: Secondary-electron yields were investigated for 28-MeV protons, 126-MeV oxygen-ions, and 182-MeV gold ions incident on 304 stainless-steel surfaces. The dependence on the incidence angle was studied in detail, and a system was developed which allows accurate measurements to be performed over a wide angular range extending to nearly grazing collisions. Electron yield estimates of interest for future accelerator applications are developed for 1-GeV protons, and the possible mitigation of deleterious effects by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 19 publications
4
35
0
Order By: Relevance
“…The electron emission coefficient is observed to vary with the ion angle of incidence θ as γ e ∝ 1/cos(θ), where d/cos(θ) is the ion path length through a thin d ≈ 2 nm thick surface layer (where the beam-induced emitted electrons originate). Similar scaling of emission with θ is observed at higher ion energies by Thieberger [13].…”
Section: B Additional Experimental Tools and Applicationssupporting
confidence: 83%
See 2 more Smart Citations
“…The electron emission coefficient is observed to vary with the ion angle of incidence θ as γ e ∝ 1/cos(θ), where d/cos(θ) is the ion path length through a thin d ≈ 2 nm thick surface layer (where the beam-induced emitted electrons originate). Similar scaling of emission with θ is observed at higher ion energies by Thieberger [13].…”
Section: B Additional Experimental Tools and Applicationssupporting
confidence: 83%
“…We found that emission scaled with the electronic component of ion stopping in stainless steel, dE/dx [14], as has been found previously at higher energies [15]. However, the emission varied more slowly with the ion angle of incidence than 1/cos(θ), unlike measurements with 1 MeV K+ [12] and higher energy ions [13]. Based on a modified Sternglass model [16], we have modeled the dependence on ion energy and the ion angle of incidence [14], evaluating a dE/dx model with the SRIM code [20].…”
Section: B Additional Experimental Tools and Applicationssupporting
confidence: 80%
See 1 more Smart Citation
“…For the PSR, for example, it is estimated that the proton loss rate is ~4x10 -6 per stored proton per turn, and that the electron yield per proton striking the wall is ~100-200 [19]. For heavy ions striking a chamber wall, such as Au 79+ used at RHIC, the electron yield is significantly higher than for protons [20]. For K + ions used in present HIF test drivers, the yield appears to be comparable to that for protons at the PSR, at least a low ion energies [21].…”
mentioning
confidence: 99%
“…The measured yields will enable us to interpret electron emission currents from electrodes in beam tubes due to beamhalo loss, and the resulting gas desorption. η e (θ), which reaches 130 at 88 o , is observed to scale as η e ∝ 1/cos(θ), (θ = 0 is normal incidence), similar to the angular dependence at higher ion energies [6]. η o (θ), measured from the pressure rise after a pulse, is less steep than 1/cos(θ), varying from 6x10 3 to 9x10 3 for 80 ≤ θ ≤ 88 o .…”
Section: Experiments and Diagnosticsmentioning
confidence: 92%